Heat Exposure and Youth Migration in Central America and the Caribbean - Baez, Javier; Caruso, German; Mueller, Valerie; Niu, Chiyu (American Economic Review, 2017)
We employ a triple difference-in-difference approach, using censuses and georeferenced temperature data, to quantify heat effects on internal migration in Central America and the Caribbean. A 1-standard deviation increase in heat would affect the lives of 7,314 and 1,578 unskilled young women and men. The effect is smaller than observed in response to droughts and hurricanes but could increase with climate change. Interestingly, youth facing heat waves are more likely to move to urban centers than when exposed to disasters endemic to the region. Research identifying the implications of these choices and interventions available to minimize distress migration is warranted.